2017
DOI: 10.2494/photopolymer.30.483
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Zinc Oxide Nanoparticles for Electron Injection Layers in Organic Light-Emitting Devices

Abstract: We report the application of two surface modifiers, 2-(2-hydroxyphenyl)benzothiazole (BTz) and 8-quinolinol (8Qn), to electron-transporting layers (ETLs) comprising zinc oxide nanoparticles (ZnO NPs) to improve the efficiency of electron injection into light-emitting layers in organic light-emitting devices (OLEDs). BTz and 8Qn were respectively added to ZnO NP dispersions; these surface modifiers then reacted with the ZnO NPs and changed their optical properties, proving the interaction between the ZnO NPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Such modification can alter the WFs of the electrodes. Currently, various cathode modifiers have been reported. , Zhou et al have reported one of the most important studies in this decade . They modified electrodes using polyethylenimine (PEI) derivatives, including branched (PEI) and polyethylenimine ethoxylated (PEIE), and reported the considerable WF reduction of the electrodes by exploiting the alignment of the permanent dipole of these compounds on the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Such modification can alter the WFs of the electrodes. Currently, various cathode modifiers have been reported. , Zhou et al have reported one of the most important studies in this decade . They modified electrodes using polyethylenimine (PEI) derivatives, including branched (PEI) and polyethylenimine ethoxylated (PEIE), and reported the considerable WF reduction of the electrodes by exploiting the alignment of the permanent dipole of these compounds on the electrodes.…”
Section: Introductionmentioning
confidence: 99%